The Development of Socio-Emotional Inventory for Stanted Children in Indonesia: Rasch Model Analysis - Nandang Budiman; Ari Khusumadewi; Zikra; Indah Sukmawati; Afdal; Imaddudin; Ibrahim Al Hakim (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Stunting is commonly perceived as a physical issue in children, yet it also affects their psychological growth, particularly socio-emotional development. This study aims to construct a valid and reliable socio-emotional inventory for stunted children aged 4–5 years. Employing a cross-sectional quantitative design, the study involved 311 participants observed by early childhood teachers, primary school teachers, and parents, selected through convenience sampling. Data were analyzed descriptively using the Rasch model in Winstep 3.73. Findings revealed 24 valid statement items for assessing the socio-emotional aspects of stunted children. Reliability was established through person–item interaction, with a Cronbach’s Alpha of 0.73, categorized as “good”. The inventory covers dimensions of self-awareness, responsibility toward self and others, and prosocial behavior. Results suggest that the socio-emotional inventory for stunting cases demonstrates strong psychometric qualities, making it suitable for evaluating socio-emotional conditions of stunted children, and offering a useful tool for early intervention and educational planning. Keywords: stunting, socio-emotional development, inventory validation, rasch model, early childhood education